Selecting Value Chain in Ethiopia - Dawide, Tofik Abdella (Discoveries in Agriculture and Food Sciences, 2023)
Agribusiness and value chain development (AVCD) features prominently in development programming aimed at stimulating economic growth and increasing the competitiveness of the agricultural sector. And value chain selection is one of an approach that used to develop agribusiness and value chain in emerging economic country. Some of literatures found different criteria and selection process approach to select priority value chains. This study is evaluated and identify priority value chain by using porters’ competitive advantage approach with ILO of FAO impact potential value chain selection criteria for sustainable development. And the final analysis suggests that none of crops should be considered “priority” value-chains, since these are highly-ranked respective of how outcomes are weighted to develop agribusiness and value chain of all crops should corporate. Developing inclusive agricultural value chain system development forwarding so.